ANTIOXIDANT POTENTIAL OF PIPERIDINE CONTAINING COMPOUNDS-A SHORT REVIEW - K, Manjusha R; Begum, Shaheen; Begum, Arifa; K, Bharathi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Piperidine is a saturated heterocyclic ring, considered as a privileged scaffold in view of its role in wide range of biological activities. Piperidine is good candidate molecule for obtaining potent antioxidant agents. The planar nature of this heterocyclic nucleus allows the introduction of substituent groups at different positions on the ring. In the present review, the antioxidant profile of piperidine containing compounds has been focused. The compounds were classified into naturally occurring piperidines, unsaturated piperidines, N-substituted piperidines, piperamides, piperanols, piperidine oximes, and hydrazides.